2021
DOI: 10.1200/op.21.00147
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and Personal Consequences of the COVID-19 Pandemic on US Oncologist Burnout and Well-Being: A Study From the ASCO Clinician Well-Being Task Force

Abstract: INTRODUCTION: The COVID-19 pandemic is an unprecedented global crisis profoundly affecting oncology care delivery. PURPOSE: This study will describe the occupational and personal consequences of the COVID-19 pandemic on oncologist well-being and patient care. MATERIALS AND METHODS: Four virtual focus groups were conducted with US ASCO member oncologists (September-November 2020). Inquiry and subsequent discussions centered on self-reported accounts of professional and personal COVID-19 experiences affecting we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…A recent focus group study among ASCO oncologists found that prepandemic burnout compounds the personal and occupational stressors experienced during the pandemic and provided a number of valuable recommendations to reduce burnout including flexible time-off schedules and peer support groups. 9 The ESMO survey similarly found that working hours and availability of colleagues for emotional support were significant predictors of lower distress levels. 10 Given the struggles with isolation from colleagues described in this study, departments should integrate regular team check-ins and identify opportunities to increase collaborative practice across inpatient and outpatient services, such as using telehealth to support joint visits and virtual rounding.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent focus group study among ASCO oncologists found that prepandemic burnout compounds the personal and occupational stressors experienced during the pandemic and provided a number of valuable recommendations to reduce burnout including flexible time-off schedules and peer support groups. 9 The ESMO survey similarly found that working hours and availability of colleagues for emotional support were significant predictors of lower distress levels. 10 Given the struggles with isolation from colleagues described in this study, departments should integrate regular team check-ins and identify opportunities to increase collaborative practice across inpatient and outpatient services, such as using telehealth to support joint visits and virtual rounding.…”
Section: Discussionmentioning
confidence: 97%
“…4 Recent analyses have indicated that health professionals treating COVID-19-infected patients have been more likely to experience depression, anxiety, posttraumatic stress disorder, and other psychiatric conditions. [5][6][7][8] Surveys conducted by ASCO and ESMO have also identified negative mental health outcomes among physicians providing oncology care during the pandemic, [9][10][11] including distress, burnout, and decreased well-being. Furthermore, ESMO found that wellbeing and job performance since COVID-19 were correlated with local COVID-19 crude mortality rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…“I think that all of our colleagues are feeling a lot of burnout right now. Everybody’s seeing a lot of death and heartache and social isolation and anger that they’re not used to encountering in very new and different ways” [ 50 ] p. 431.…”
Section: Impact Of Covid-19 Pandemic On Oncology Healthcare Professio...mentioning
confidence: 99%
“…Thus, ASCO worked to develop a framework for understanding the role of this pandemic in compounding or exposing ongoing burnout among oncology clinicians. Initially captured as a goal in ASCO's Road to Recovery Report , the subsequently published report on occupational and personal consequences of the COVID-19 pandemic on US oncologist burnout and well-being identified significant distress, practice alterations such as early retirement, and signs of resiliency among clinicians 32 . A follow-up survey is planned for 2022 to assess the ongoing consequences of the public health emergency.…”
Section: Emerging From the Pandemicmentioning
confidence: 99%